Epicardial Brugada syndrome ablation unmasking inferior J waves. Issue 11 (1st June 2017) - Lee, Adam; Kohler, Heidi; Wright, Daniel; Haqqani, Haris M.
Abstract: Patients with Brugada syndrome are at risk of life‐threatening ventricular arrhythmias. Epicardial substrate ablation for Brugada syndrome has been described as a means of controlling these arrhythmias and recent reports describe elimination of the Brugada phenotype with ablation. We describe a unique case in which a patient developed inferior J waves with an early repolarization‐type electrocardiogram following successful epicardial infundibular substrate ablation (which eliminated the Brugada syndrome electrocardiogram on ajmaline challenge). We discuss the likely underlying pathophysiology responsible for this phenomenon, its relationship to the anatomic obstacles encountered during epicardial ablation, and the implications for long‐term arrhythmic risk.